Pengaruh Lingkungan Pemasaran Terhadap Kinerja Pemasaran Melalui Strategi Pemasaran Pada Usaha Jasa Laundry Di Surabaya - Sucitro, Robby (Kajian Ilmiah Mahasiswa Manajemen, 2013)
Laundry business development at this time is very fast. The owner laundry services founded their business in a variety of areas, both residential as well as around it. Good assortment of customers in the high and low levels. The benefits of this laundry services not only the owner but also useful laundry services to consumers. More precisely the mother-housewife who became lighter in housework. The purpose of this study was to determine the effect of the marketing environment on marketing performance through marketing strategies on laundry services business in Surabaya. The Techniques used in the sampling in this study was purposive sampling, Meanwhile, the analytical techniques used in this research is the method of Structural Equation Modeling (SEM) with LISREL 8.70 program. Respondents are drawn from an owner laundry services in Surabaya.